Decision Support System for Determining the Level of Employee Salary Increase at PT. Srikandi Inti Lestari Medan by Using the Simple Additive Weighting (SAW) Method - Bayu Saputra (Institute of Computer Science, 2020)
Employees are seen as one of the company's important assets and need to be managed and developed to support the survival and achievement of company goals. One form of employee organization that can be carried out by the company is to provide remuneration or salary payments suitable for employees. Salary increases greatly affect employee motivation and productivity in carrying out and completing their work. To determine the amount of salary increase, a system is needed that can support decision making by managers. Utilization of decision support systems using Simple Additive Weighting (SAW) method is very helpful for managers in making decisions that are faster and more accurate. The basic concept of SAW method is look for weighted sums of performance ratings on each alternative and on all attributes that require a decision matrix normalization process (X) a scale that can be compared with all available alternative ratings. This method was chosen because it was able to select the best alternative from a number of alternatives based on the specified criteria. Research was carried out by examining the weights for each attribute and then ranking it which would determine the optimal alternative.